Faktor yang Berhubungan Dengan Kejadian Tuberkulosis pada Pasien yang Berkunjungn ke Puskesmas Dinoyo Kota Malang - Hapsari, Dewi Anggia; Yunus, Moch; Gayatri, Rara Warih (citeus, 2020)
Tuberculosis is an infectious disease caused by mycobacterium tuberculosis. The Centers for Disease Control and Prevention (CDC) says about 1.9 billion or one third of the world's population has been infected with tuberculosis. WHO recorded in 2011 as many as 8.7 million people sick because of tuberculosis and 1.4 million of them died due to tuberculosis. Given that tuberculosis is an infectious disease, therefore the environment has a role in the transmission of tuberculosis. The purpose of this research is to know the correlation of education level, income level and home condition with the incidence of tuberculosis in patients who visited the Puskesmas Dinoyo Malang City during May to June 2017.This research was conducted by using analytic observational study with cross sectional approach. A sample size of 44 people who have met the inclusion criteria, obtained by accidental sampling. The research was conducted by distributing questionnaires and doing direct observation to respondent's house. From 44 respondents, 26 of them (59,1%) were exposed to tuberculosis, the highest level of education was high school graduation as many as 18 people (40,9%), the level of income of majority of respondents below UMR was 27 people (61,4% ) and condition house in healthy condition counted 25 people (56,8%). The result of chi square test with α = 0,05 is education level of elementary school (p = 0,009) and high school education level (p = 0,001), income level below UMR (p = 0,000) and house condition (p = 0,001 ). There is a significant correlation between education level, income level and house condition with the incidence of tuberculosis in patients who visited Puskesmas Dinoyo Malang City.